A people stronger : the collectivization of MSM and TG groups in India - Singh, Suneeta (SAGE, 2013)
The discourse on sexuality and alternate sexualities in India's public space has grown in volume, and those who practice same-sex relations have become more visible. Among these are the MSM (men who have sex with men) and TG (transgender) groups. A People Stronger provides a comprehensive analysis of the collectivization efforts of these groups in India. The book describes the journey of a marginalized closeted community and its gradual assumption of a place within society, providing compelling examples of social action. Further, through its description of the 'coming out' of the insular society of hijras, it provides useful insights into real-world acculturation. The book is also a riveting history of these communities in India from pre-Vedic times to the present. The fundamental principle guiding this work is that sexual minority groups must get acceptance within the framework of India's constitution of their existence as citizens of the country, equal in dignity and in rights, having the same sovereignty as other citizens and of the same realization of their social identities.